Locating L2 English Writing Centers in German Universities - Bonazza, Ruth (Journal of Academic Writing, 2016)
As L2 English writing support services, including writing centers, expand into different linguistic and national contexts, it becomes imperative for literacy brokers (Lillis and Curry 2006) and literacy managers (Bräuer 2012) to reflect on the uses and limitations of existing writing support models and teaching approaches. This paper presents the findings from a project that tracked the growth of L2 English writing centers in German universities from 2013-2015, locating their emergence within changes in the German academic landscape. Using data taken from questionnaires and interviews, this paper locates and explores ten L2 English writing centers in Germany, focusing on their aims; organizational models and teaching approaches; staffing and funding; key university partnerships; offers; and reflections on the future. It is hoped that these collated experiences could be of interest to other L2 English centers developing in different countries and language contexts.